Breathing in the larval and adult stages: an analytical study of breathing changes with age - Najiyah S. Husayn; Randah A. Ahmed (African Journal of Advanced Pure and Applied Sciences, 2025)
Normal respiration processes in amphibians change remarkably as tadpoles transform into adult creatures. Multiple factors that affect frog respiratory adaptations will be studied during this investigation. The respiration system of tadpole’s functions through gills before the transformation into adult frogs which uses pulmonary and cutaneous methods. The research makes use of spirometry together with histological analysis and environmental monitoring to determine differences in how tadpoles and adult frogs breathe and the efficiency of their oxygen absorption. Tadpoles experience rapid respiration along with high oxygen consumption levels yet adult frogs perform better oxygen uptake through their lungs and skin since they need to survive on land. The respiratory efficiency of frogs is heavily influenced by environmental conditions of temperature and humidity which in turn affect their developmental transition. The research results demonstrate amphibian respiration adapts chronically while establishing developmental and environmental influences which optimize oxygen intake. The current study enhances amphibian scientific knowledge about physiology while revealing strategies that enable their ecological and evolutionary natural history.